Enhancement of nutrients removal and biomass accumulation of Chlorella vulgaris in pig manure anaerobic digestate effluent by the pretreatment of indigenous bacteria. (May 2021) - Gu, Zhiqiang; Liu, Yuhuan; Zou, Guyue; Zhang, Qi; Lu, Rumeng; Yan, Hongbin; Cao, Leipeng; Liu, Tongying; Ruan, Roger
Graphical abstract: Highlights: Inhibitor in anaerobic digestate followed the order of COD > NH4 + -N > turbidity. Algal growth was enhanced by12.54% after pretreated the anaerobic digestate. Lipid content of C. vulgaris increased by 6.90% in pretreated anaerobic digestate. 87.59%, 65.87%, 65.29% of COD, TP, turbidity in anaerobic digestate were removed. Abstract: High concentrations of pollutants in pig manure anaerobic digestate effluent (PMADE) can severely inhibit microalgal growth. In this study, two types of PMADE (PMADE-1, PMADE-2) were pretreated with indigenous bacteria which were selected from PMADE to alleviate their inhibition for the growth of Chlorella vulgaris. Indigenous bacteria could decrease 34.04% and 47.80% of total phosphorus (TP) and turbidity in PMADE-1, and 80.81%, 43.27%, and 57.51% of COD, TP, and turbidity in PMADE-2, respectively. And no significant reduction of NH4 + -N in both PMADE after 5 days pretreatment occurred. C. vulgaris failed to grow in unpretreated PMADE-2. Pretreatment of PMADE with indigenous bacteria could remarkably promote nutrients removal and cell growth of C. vulgaris compared to the unpretreated PMADE. The order of abiotic stress in the studied PMADE was COD > NH4 + -N > turbidity, and it is appropriate to pretreat the PMADE with indigenous bacteria for 2–3 days.